Examination of Decision-Making Levels of Individual Sports Persons (Table Tennis Example) - Ünal Türkçapar, Tahmira Sabraliyeva (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: This study is to determine how the decision-making levels of individuals who play table tennis in Kyrgyzstan are shaped. Material and Methods: Scanning method was used in this study. This study has a descriptive and inferential nature. The study group of this research consists of 369 participants, 168 women and 201 men, who played table tennis in Kyrgyzstan in 2020. The study was shaped on the basis of voluntary participation criteria. In this study, a personal information form prepared by the researcher and a Decision Making Scale were used to collect data. Personal information form; Gender, age, education level, how many years have you been a licensed athlete, monthly income level, place of residence, profession and do you have any harmful habits? In addition, in order to determine the decision-making levels of the participants; The decision making scale (MDMS I-II) prepared by Mann et al. (1998) and adapted into Turkish by Deniz (2004) was used. The obtained data were transferred to the computer environment and evaluated with the SPSS 21.0 statistical program. Results: There is no significant difference in the decision-making levels of the table tennis players participating in the study in terms of gender, year of sport, education level, monthly income level and profession, but it was concluded that there was a significant difference in the do you have any harmful habits? variable. Conclusion: It has been concluded that the variables of gender, year of sport, education level, monthly income level and profession are not the determining factors of the decision-making levels of table tennis players.